(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the benefits of incorporating proverbs into classroom lessons. It explores how using proverbs can enhance students’ understanding of language, culture, and critical thinking skills. Additionally, it examines the role of proverbs in promoting social and emotional learning, as well as fostering creativity and communication skills among students.